Effectiveness of the ASSURE Instructional Model Integrated with Wordwall in Promoting Students’ Learning Engagement in Akidah Akhlak - Harahap, Nur Aisyah Finanda; Zulaikhah, Siti; Hasanah, Uswatun (Universitas Muhammadiyah Mataram, 2026)
The teaching of Aqidah Akhlak at the MTs level remains predominantly characterized by conventional approaches with limited utilization of instructional media, resulting in suboptimal development of students’ learning engagement. Furthermore, the use of gamification-based media, such as Wordwall, in Aqidah Akhlak instruction is still minimal and has not been systematically integrated, despite its considerable potential to enhance student involvement and active participation.This study explores the effectiveness of a technology-enhanced instructional approach that combines the ASSURE learning model with the Wordwall gamification platform to promote student learning activeness in Akidah Akhlak education. A quantitative quasi-experimental research design was implemented. The study involved seventh-grade students from MTs Darul Huda Bandar Lampung, where two classes were randomly selected and assigned to experimental and control conditions. Student learning activeness data were obtained using a validated questionnaire with satisfactory internal consistency (α = 0.754). Statistical analysis procedures encompassed assumption testing, including normality and homogeneity tests, followed by an independent samples t-test. The results demonstrate a statistically significant difference in learning activeness between students taught using the ASSURE–Wordwall integration and those receiving conventional instruction, with a significance value of 0.011 (p < 0.05). Students exposed to the integrated instructional model exhibited higher levels of engagement, as reflected in their participation in questioning, collaborative discussions, interactive quizzes, and reflective learning activities. The novelty of this research lies in the application of the ASSURE instructional design model in conjunction with game-based Wordwall media within the context of Akidah Akhlak instruction at the Islamic junior secondary school level. By positioning learning activeness as the primary outcome variable, this study addresses a gap in existing literature. The findings contribute to the theoretical discourse on digital instructional design and offer practical guidance for educators in developing Islamic religious education that is interactive, structured, and responsive to the competencies required in 21st-century learning environments.